Hsp90 middle domain phosphorylation initiates a complex conformational program to recruit the ATPase-stimulating cochaperone Aha1 - Xu, Wanping (Nat Commun, 2019)
Complex conformational dynamics are essential for function of the dimeric molecular chaperone heat shock protein 90 (Hsp90), including transient, ATP-biased N-domain dimerization that is necessary to attain ATPase competence. The intrinsic, but weak, ATP hydrolyzing activity of human Hsp90 is markedly enhanced by the co-chaperone Aha1. However, the cellular concentration of Aha1 is substoichiometric relative to Hsp90. Here we report that initial recruitment of this cochaperone to Hsp90 is markedly enhanced by phosphorylation of a highly conserved tyrosine (Y313 in Hsp90α) in the Hsp90 middle domain. Importantly, phosphomimetic mutation of Y313 promotes formation of a transient complex in which both N- and C-domains of Aha1 bind to distinct surfaces of the middle domains of opposing Hsp90 protomers prior to ATP-directed N-domain dimerization. Thus, Y313 represents a phosphorylation-sensitive conformational switch, engaged early after client loading, that affects both local and long-range conformational dynamics to facilitate initial recruitment of Aha1 to Hsp90.